Sleep disturbances and non-cyclical breast pain: Where to break the vicious cycle? - Basım, Pelin; Tolu, Sena (Springer Heidelberg, 2022)
Purpose: This study aimed to assess the sleep quality of patients with the complaint of non-cyclical breast pain (NCBP), compare them to a healthy control group, and analyze the interrelationship of sleep quality with pain, anxiety, depression, and quality of life. Methods: This cross-sectional study was conducted in consecutive women presenting to the general surgery clinic between May 2020 and December 2020. Patients diagnosed with NCBP formed one group for study and 44 receiving routine well-woman care formed the control group. Evaluations were undertaken using the Nottingham Health Profile (NHP), short-form McGill Pain Questionnaire (SF-MPQ), Hospital Anxiety and Depression Scale (HADS), and Pittsburgh Sleep Quality Index (PSQI). Results: Of 160 consecutive patients, 116 were diagnosed with NCBP and 44 controls. Poor sleep quality (PSQI > 5) was present in 59% (n = 69) of the women with NCBP and 38% (n = 17) of the controls (p = 0.018). According to PSQI global score, overall sleep quality was significantly lower in the NCBP group compared to the control group (p < 0.007). Sleep latency, sleep duration, and daytime dysfunction were the major components determining the PSQI global score (p = 0.004, p = 0.004, and p < 0.001, respectively). The correlation matrix revealed a statistically significant correlation between the HAD-A, HAD-D, and SF-MSQ and NHP subgroups and PSQI global score in the NCBP group (p < 0.001) whereas this significant correlation was detected with only the NHP subgroups among the controls. Conclusions: A considerable proportion of NCBP patients, regardless of sensory or affective characteristics and trajectory of pain, experience significant sleep disturbances. Further studies should be conducted to evaluate the existence of central sensitization syndrome in NCBP patients to determine the required pharmacological treatment.
Keywords: Non-Cyclical Breast Pain; Sleep Disorders; Anxiety; Depression; Quality of Life; Central Sensitization